1993
DOI: 10.1029/93jd00322
|View full text |Cite
|
Sign up to set email alerts
|

The meteorological environment of the tropospheric ozone maximum over the tropical South Atlantic Ocean

Abstract: Atmospheric flow patterns are examined over the South Atlantic Ocean where a maximum of tropospheric ozone has been observed just west of southern Africa. We investigate the flow climatology during October and perform a case study for 6 days during October 1989. Analyses from the European Center for Medium‐Range Weather Forecasting are employed, and a high‐resolution global spectral model is used to prepare forecasts during the period. Horizontal and vertical motions are examined and used to prepare three‐dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 52 publications
3
39
0
Order By: Relevance
“…2). The coincidence of biomass burning and cloud convection was proposed as a key mechanism for the export of biomass burning emissions far away from the source regions (Krishnamurti et al, 1993;Chatfield et al, 1996;Pickering et al, 1996;Folkins et al, 1997;Jenkins et al, 1997;Trentmann et al, 2006;Sauvage et al, 2007a;Sauvage et al, 2007b) with potential intrusions into the upper troposphere and stratosphere (Fromm and Servranckx, 2003;Jost et al, 2004). Other mechanisms have been proposed for the vertical transport of biomass burning emissions: convergence between the baroclinic low-level circulations associated with the AEJ-S and the equatorward branch of the Hadley cell (Sauvage et al, 2007c) and the vertical turbulent mixing favored by the intertropical interoceanic front (Chatfield et al, 1996;Bachmeier and Fuelberg, 1996;Delmas et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…2). The coincidence of biomass burning and cloud convection was proposed as a key mechanism for the export of biomass burning emissions far away from the source regions (Krishnamurti et al, 1993;Chatfield et al, 1996;Pickering et al, 1996;Folkins et al, 1997;Jenkins et al, 1997;Trentmann et al, 2006;Sauvage et al, 2007a;Sauvage et al, 2007b) with potential intrusions into the upper troposphere and stratosphere (Fromm and Servranckx, 2003;Jost et al, 2004). Other mechanisms have been proposed for the vertical transport of biomass burning emissions: convergence between the baroclinic low-level circulations associated with the AEJ-S and the equatorward branch of the Hadley cell (Sauvage et al, 2007c) and the vertical turbulent mixing favored by the intertropical interoceanic front (Chatfield et al, 1996;Bachmeier and Fuelberg, 1996;Delmas et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The seasonal contrast is greatest in the Atlantic with maximum values during austral spring over the southern tropical Atlantic. The high values of TCO in this region during austral spring have been attributed to biomass burning, lightning, and dynamics as part of TRACE-A [Krishnamurti et al, 1993[Krishnamurti et al, , 1996Jacob et al, 1996;Pickering et al, 1996;Thompson et al, 1996]. Outside the tropics, the zonal contrast decreases but seasonal contrast intensifies over all longitudes.…”
Section: Comparison With the Geos-chem Modelmentioning
confidence: 99%
“…The stratosphere is a third source region through stratosphere-troposphere exchange (STE) by, for example, tropopause folds [Shapiro, 1980]. Apart from the studies from Pacific Exploratory Mission-West (PEM-West) and Measurements of Ozone by Airbus In-Service Aircraft (MOZAIC) [Newell et al, 1996[Newell et al, , 1999Browell et al, 1996;Wu et al, 1997] and PEM-Tropics [Fenn et al, 1999], other studies also indicated stratospheric influences in the tropical troposphere [Krishnamurti et al, 1993;Kley et al, 1996;Suhre et al, 1997;Cammas et al, 1998;Taupin et al, 1999]. Shear-induced differential advection can cause tracer surfaces to stretch which leads to quasi-horizontal laminae-like tracer structures [see Appenzeller and Holton, 1997, Figure 1; Ambaum, 1997].…”
Section: Introductionmentioning
confidence: 99%